Exploring the influence of perceived classroom environment on learner autonomy in a Chinese EFL learning context - Yang, Shiyu; Liu, Liyan; Hunt, Neil (Frontiers in Psychology, 2022)
Developing learner autonomy has been a critical task in English teaching that requires a clear understanding of the feature of classroom environment. This study aims to examine how senior high school students perceive classroom environment and learner autonomy, and how classroom environment exerts its influence on learner autonomy in Chinese EFL learning context. Participants (N=565) from 15 classes located in northeast of China were selected to fill in an adapted version of What is Happening in This Class (WIHIC) and English Autonomous Learning Ability scale. Interview was conducted to confirm and illustrate the quantitative findings. The results revealed that senior high students had favorable perceptions of English classroom environment and learner autonomy. Grade differences exist in their perceptions. Moreover, we found that 53.7% of the variance in learner autonomy was accounted for by students’ perceptions of English classroom environment, which indicate English classroom environment had significantly positive effects on learner autonomy. Specifically, task orientation, student involvement, teacher support and finding references are strong predictors to learner autonomy. The possibles reasons for the findings are discussed.